Constitutional mismatch repair deficiency and childhood leukemia/lymphoma – report on a novel biallelic MSH6 mutation - Tim Ripperger; Carmela Beger; Nils Rahner; Karl W. Sykora; Clemens L. Bockmeyer; Ulrich Lehmann; Hans H. Kreipe; Brigitte Schlegelberger (Haematologica, 2010)
Biallelic mutations of mismatch repair genes cause constitutional mismatch repair deficiency associated with an increased risk for childhood leukemia/lymphoma. We report on a case with constitutional mismatch repair deficiency caused by a novel MSH6 mutation leading to a T-cell lymphoma and colonic adenocarcinoma at six and 13 years of age, respectively. A review of the literature on hematologic malignancies in constitutional mismatch repair deficiency showed that in almost half of the 47 known constitutional mismatch repair deficiency families, at least one individual is affected by a hematologic malignancy, predominantly T-cell lymphomas. However, diagnosing constitutional mismatch repair deficiency may be difficult when the first child is affected by leukemia/lymphoma, but identification of the causative germline mutation is of vital importance: (i) to identify relatives at risk and exclude an increased risk in non-mutation carriers; (ii) to prevent hematopoietic stem cell transplantation from sibling donors also carrying a biallelic germline mutation; and (iii) to implement effective surveillance programs for mutation carriers, that may reduce constitutional mismatch repair deficiency-associated mortality.